Participatory Design Model for Community-Based Rooftop Urban Farming - Muhammad Mutammam Musthofa; Ronalmanto Ronalmanto; Listhia Dwi Orisavianti; Indrika Dwi Febianti (Universitas Islam Raden Rahmat, Malang, 2026)
Rapid urbanization demands innovative approaches to overcome spatial limitations and enhance urban food security, positioning rooftop urban farming as a strategic and sustainable solution. Yet, the long-term success of such initiatives is frequently constrained by social and managerial challenges. This study proposes an optimized Participatory Design Model to strengthen both technical sustainability and community ownership in rooftop urban farming. Adopting a qualitative approach within a Participatory Action Research (PAR) framework, data were collected through Focus Group Discussions (FGDs). The analysis synthesized user driven priorities into a design model that emphasizes reducing maintenance burdens and enhancing social utility. Key strategies include the selection of planting systems with high operational simplicity specifically a combination of hydroponic and soil based media and the incorporation of design elements that facilitate community engagement and interaction. The findings underscore that co-creation is fundamental to developing resilient, user centered rooftop farming systems that minimize maintenance challenges while reinforcing long-term community commitment.